Changes in dream features across the first and second waves of the Covid‐19 pandemic. (22nd June 2021) - Conte, Francesca; Rescott, Marissa Lynn; De Rosa, Oreste; Cellini, Nicola; Coppola, Alessia; Cerasuolo, Mariangela; Malloggi, Serena; Giganti, Fiorenza; Ficca, Gianluca
Summary: Research during the Covid‐19 pandemic has highlighted its significant impact on dreaming. Here we address changes in dream features both during the first wave, when the Italian government imposed a total lockdown, and the second wave (autumn 2020), when a partial lockdown was effected. In April 2020 (total lockdown), 1, 622 participants (Mage  = 34.1 ± 13.6 years; 1171F) completed an online survey including the Pittsburgh Sleep Quality Index and a set of questions on dream features and their possible changes relative to the month preceding the lockdown (pre‐total lockdown). In November 2020 (partial lockdown), 214 participants (Mage  = 36.78 ± 14.2 years; 159F) from the previous sample completed the same survey. Approximately half of the subjects reported increased or decreased dream frequency (30.5% and 21.8%), length (27.1% and 15.8%) and vividness (31.5% and 17.1%) during total lockdown as well as during partial lockdown (frequency: 30.3% and 13.5%; length: 23.3% and 12.6%; vividness: 31.6% and 24.1%). Dream affect became significantly more negative in total lockdown relative to pre‐total lockdown and in partial lockdown relative to pre‐partial lockdown (both p  < .001). Both in total lockdown and partial lockdown, increased negative dream emotionality significantly predicted changes in dream frequency, length and vividness, and was significantly predicted, in turn, by worsened sleep quality. Our data confirm that dream features are significantly affected by major life changes such as those imposed by a pandemic. The fact that between lockdowns negative dream affect returned almost to baseline level suggests that dream emotionality is closely related to lifestyle and wake‐time emotional changes. Also, our findings point to a modulating role of sleep quality on dream emotionality.